(untitled) (Journal of Asian Development Studies, 2019)
The main theme of the research is to analyze the concept of national security. The study focuses on the factors relating to the national security and its implications. It also highlights the internal and external factors directly and indirectly threats towards the Pakistan’s national security. The approach is descriptive and analytical. The sources are original and secondary. The findings and suggestions are in the end.